Translating victims' perceptional variations into policy recommendations in the context of riverine floods in a tropical region. (March 2023) - Islam, Aznarul; Ghosh, Susmita; Sarkar, Biplab; Nandy, Sweety; Guchhait, Sanat Kumar
Abstract: The study of human behaviour and perceptions regarding flood management strategies can help enhance the adaptive capacity of flood victims. An in-depth questionnaire survey was executed over a statistically significant sample size of 2382 households to assess the perception of flood victims regarding 27 parameters of existing flood management strategies in a tropical flood-prone region like the Mayurkashi River Basin, India. The techniques such as ridit analysis, spatial autocorrelation, Kruskal-Wallis test, principal component analysis, and Lewin's equation of human behaviour have been used to reveal the complexity of the perceptional pattern. The results found that there are four existing flood management strategies (1) local community initiatives, (2) initiatives taken by the government and others, (3) joint (local community and government) structural, and (4) joint non-structural measures. Ridit analysis depicted that perceptional variations are relatively higher for the indicator under government and other initiatives while relatively lower for the indicators under the local community initiatives. The higher perceptional variations for the parameters of the government initiatives imply the existence of a top-down approach. However, parameters under community initiatives register a lower perceptional variability indicating the relative objectivity in their opinions. The study also found that characteristics of perceivers (socio-economic traits), situation (flood event), and target (nature of management strategies) have been instrumental in driving the perceptional variation. Finally, the study emphasizes the need for the blending of the bottom-top approach with the existing top-down approaches in village-level planning in a participatory manner. Graphical abstract: Image 1 Highlights: A novel approach is embraced to translate the flood victims' perceptional variations into policy recommendations. Perceptional variations are revealed using ridit analysis, Kruskal-Wallis index and some geostatistical measures. Perceptional variations are higher for strategies undertaken by government and others compared to local community initiatives. The spatiality in the perception is driven by the characteristics of the perceivers, flood situation, and target. The bottom-top approach is recommended for micro-level planning in the study area.